Recovery of platelet function after discontinuation of clopidogrel treatment in healthy volunteers - Weber, Artur-Aron (Blackwell Science Inc, 2001)
AIMS: To study the recovery of platelet function after discontinuation of clopidogrel treatment in healthy volunteers. METHODS: Ten healthy volunteers were treated with clopidogrel (75 mg day(−1)) for 7 days. CD62P expression and PAC-1 binding were measured by flow cytometry. RESULTS: Adenosine diphosphate (ADP, 30 µm)-induced platelet responses were almost completely inhibited by clopidogrel. After discontinuation of the drug, platelet function gradually increased and complete recovery was seen 7 days after the last clopidogrel dose. The mean difference (95% CI) for ADP-induced PAC-1 binding (fluorescence intensity) between baseline and 7 days after the last dose was 0.01 (0.61, −0.59). Single cell analysis provides direct evidence for an irreversible mode of action of clopidogrel. CONCLUSIONS: This is the first report to directly demonstrate irreversibility of clopidogrel action in humans.